Front Cover. Issue 3 (1st February 2023) - Rossing, Peter; Garweg, Justus G.; Anker, Stefan D.; Osonoi, Takeshi; Pitt, Bertram; Rosas, Sylvia E.; Ruilope, Luis Miguel; Zhu, Dalong; Brinker, Meike; Finis, David; Leal, Sergio; Schmelter, Thomas; et al.
Abstract : The outside front cover image is based on the Research Letter Effect of finerenone on the occurrence of vision‐threatening complications in patients with non‐proliferative diabetic retinopathy: Pooled analysis of two studies using routine ophthalmological examinations from clinical trial participants (ReFineDR/DeFineDR) by Peter Rossing MD et al., https://doi.org/10.1111/dom.14915 .